It's Not What You Expected! The Surprising Nature of Cleft Alternatives in French and English - Destruel, Emilie; Beaver, David I.; Coppock, Elizabeth (Frontiers in Psychology, 2019)
While much prior literature on the meaning of clefts – such as the English form ‘It is X that Z’ – concentrates on the nature and status of the exhaustivity inference (‘nobody/nothing other than X Z’), we report on experiments examining the role of the doxastic status of alternatives on the naturalness of c’est-clefts in French and and it-clefts in English. Specifically, we study the hypothesis that clefts indicate a conflict with a doxastic commitment held by some discourse participant. Results from naturalness tasks suggest that clefts are improved by a property we term ‘contrariness’ (along the lines of Zimmermann, 2008). This property has a gradient effect on felicity judgments: the more strongly interlocutors appear committed to an apparently false notion, the better it is to repudiate them with a cleft.